2013
DOI: 10.1177/0954411913494325
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid learning control for improving suppression of hand tremor

Abstract: Patients with hand tremors may find routine activities such as writing and holding objects affected. In response to this problem, an active control technique has been examined in order to lessen the severity of tremors. In this article, an online method of a hybrid proportional-integral control with active force control strategy for tremor attenuation is presented. An intelligent mechanism using iterative learning control is incorporated into the active force control loop to approximate the estimation mass par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The inaccuracy in the detection of PD might have some possible reasons that include the variability in the severity of PD across patients, the sensor’s intrinsic uncertainty, and the fact that some patients may consciously or subconsciously suppress their tremors during the experiment. In previous studies, [ 37 ] and [ 38 ], PD tremor is considered and reported as a single frequency signal, and the fundamental frequency ranges between 4 to 12 Hz. However, the results in [ 30 ] showed that PD tremor consists of several harmonics.…”
Section: Discussionmentioning
confidence: 99%
“…The inaccuracy in the detection of PD might have some possible reasons that include the variability in the severity of PD across patients, the sensor’s intrinsic uncertainty, and the fact that some patients may consciously or subconsciously suppress their tremors during the experiment. In previous studies, [ 37 ] and [ 38 ], PD tremor is considered and reported as a single frequency signal, and the fundamental frequency ranges between 4 to 12 Hz. However, the results in [ 30 ] showed that PD tremor consists of several harmonics.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, the I and D actions were excluded because both actions could cause the current control system to amplify the measurement, making the control system unable to run properly, thus producing no significant result. The variations of P values were set in the range of maximum voltage that the LVCA can experienced [16], [21], [22].…”
Section: Designing Controller 21 P Controllermentioning
confidence: 99%
“…Herrnstadt and Menon used proportional-integral-derivative (PID) controller to obtain 99.8% tremor vibration reduction [15]. Besides that, As'arry et al had also managed to achieve 98.25% tremor vibration reduction using PI+AFCAIL [16]. Meanwhile, Stone et al and Lavu and Gupta obtained 20% to 60% tremor suppression in 6-13 Hz bandwidth and 83.4% tremor suppression respectively by using PID [17], [18].…”
mentioning
confidence: 99%
“…This frequency range is selected properly to conserve the frequencies interest of a tremor which is in a range of 3-12Hz [4] and at the same time eliminate the noise. The signal processing and control part were done with LabVIEW graphical user interface software package and for faster online control, a low level programming environment is necessary to reduce computational buffering [5].…”
Section: System Descriptionmentioning
confidence: 99%